Mineralizing Gelatin Microparticles as Cell Carrier and Drug Delivery System for siRNA for Bone Tissue Engineering - Sandra Hinkelmann; Alexandra H. Springwald; Sabine Schulze; Ute Hempel; Franziska Mitrach; Christian Wölk; Michael C. Hacker; Michaela Schulz-Siegmund (MDPI AG, 2022)
The local release of complexed siRNA from biomaterials opens precisely targeted therapeutic options. In this study, complexed siRNA was loaded to gelatin microparticles cross-linked (cGM) with an anhydride-containing oligomer (oPNMA). We aggregated these siRNA-loaded cGM with human mesenchymal stem cells (hMSC) to microtissues and stimulated them with osteogenic supplements. An efficient knockdown of chordin, a BMP-2 antagonist, caused a remarkably increased alkaline phosphatase (ALP) activity in the microtissues. cGM, as a component of microtissues, mineralized in a differentiation medium within 8-9 days, both in the presence and in the absence of cells. In order to investigate the effects of our pre-differentiated and chordin-silenced microtissues on bone homeostasis, we simulated in vivo conditions in an unstimulated co-culture system of hMSC and human peripheral blood mononuclear cells (hPBMC). We found enhanced ALP activity and osteoprotegerin (OPG) secretion in the model system compared to control microtissues. Our results suggest osteoanabolic effects of pre-differentiated and chordin-silenced microtissues.